Możliwości rozwoju potencjału twórczego dziecka w instytucjach lokalnych - Kasprzak, Michlina (Studia Edukacyjne, 2018)
In this article, the main goal is to present on the basis of own scientificobservations different principles of developing the child’s creative potential. The author presents three elements: encouraging, identifying and fostering in the context of child’s creative potential and then she presents three perspective of opportunities for development child’s creative potential in the local institutions for children. In summary she write a short concept about the opportunities for development to creativity of each child from the disfavoured backgrounds.